Primary progressive multiple sclerosis: progress and challenges. Issue 10 (16th February 2013) - Rice, Claire M; Cottrell, David; Wilkins, Alastair; Scolding, Neil J
Abstract : Primary progressive multiple sclerosis (MS) has long been recognised as presenting great difficulties to our management of what is increasingly a treatable neurological disease. Here we review some basic and clinical aspects of primary progressive MS, and describe how the disorder in fact offers powerful insights and opportunities for better understanding multiple sclerosis, and from a practical perspective an invaluable clinical substrate for studying and treating progressive disability in MS. Difficult hurdles remain, however, and these too are reviewed.